The Battle Continues: An Interpretative Phenomenological Analysis of the Experiences of Multidrug-Resistant Tuberculosis (MDR-TB) Patients - Teh, Lota A (Archīum Ateneo, 2018)
The World Health Organization cites the Philippines as one of the countries worldwide that continues to have a high burden of multidrug-resistant tuberculosis (MDR-TB), with high rates of infected Filipinos. This study investigated the lived experiences of individuals with MDR-TB. Using a qualitative method, the study documented the experiences and meaning-making of eight Filipino adults aged 26–50 who were between the third and ninth month of directly observed treatment. Data from semi-structured interviews were analyzed using interpretative phenomenological analysis that yielded five superordinate themes: (1) the recurrence of tuberculosis (TB) symptoms and the trauma of being diagnosed with MDR-TB; (2) experiences of confronting the reality of being infected with MDR-TB; (3) barriers to long-term treatment adherence; (4) significance of social support; and (5) coping with MDR-TB. These themes describe the subjective experiences of patients battling an infectious disease who were undergoing long-term outpatient treatment. The significance and implications of the findings toward a more comprehensive program of interventions for MDR-TB patients are discussed.